Application Of The Problem Based Learning (PBL) Model Help With Mind Mapping To Improve Student Activeness And Learning Outcomes - Apira, Nadia; Zainal, Andri; Ruslan, Dede; Hanu, La; Ramdhansyah, Ramdhansyah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The problem in this research is the low activity and learning outcomes. The purpose of this research is to determine the improvement of activity and learning outcomes of the eleventh-grade students of SMKN 1 Medan through the implementation of Problem-Based Learning model assisted by Mind Mapping. This study was conducted at SMKN 1 Medan. The subject of this research was the students of class XI AKL 3, totaling 32 students. The object of this research is the Problem Based Learning model assisted by Mind Mapping. This research was conducted in two cycles. The data collection techniques in this research are the observation sheets for learning activity and tests of learning outcomes. The data analysis techniques for this research are quantitative data analysis and qualitative data analysis. From the student activity observation sheet in cycle I, there were 15 (46.87%) who fell into the very active and active categories. In cycle II, the number of students categorized as very active and active increased to 31 students (96.87%) and has met the success indicator of ≥75%. From the analysis of the data obtained, the test results showed an average score of the Pre Test as 76.09 with 14 students (43.75%) achieving mastery, and in the Post Test of cycle I, the average score was 81.09 with 28 students (87.5%) achieving mastery. This improved further in the Post Test II with an average score of 90.46, with 32 students (100%) achieving mastery, meeting the success indicator of ≥85%. Based on this analysis, it can be concluded that the implementation of the Problem Based Learning (PBL) model assisted by Mind Mapping can increase student activity and learning outcomes at SMKN 1 Medan.